Phelipanche cingularum (Orobanchaceae), a new species from southern France - Croze, Thomas; Carlón Ruiz, Luis; Tison, Jean-Marc; Michaud, Henri; Molina, James; Moreno Moral, Gonzalo (Phytotaxa, 2024)
A new species of Phelipanche has been discovered in various steep places in southern France at meso- and supra-mediterranean levels. It is always parasitic on Brassicaceae, almost exclusively on Hesperis laciniata, a plant that had never been reported as host for any Orobanchaceae previously. The new species, named Phelipanche cingularum for its rocky ledge (cingula) habitat, is described and illustrated. Diagnostic characters against up to 16 presumably related species are given. We also present the results of molecular analyses well-supporting its independence. The distribution and the unusual ecology of the plant are considered and illustrated, and its conservation status is evaluated.